Cryptococcus neoformans Isolated from burn Patients in Burn Hospital in Baghdad. - Jassem, Inaam K.; Mohammed, Sudad J.; Tawfeq, Tawfeq W.; Karhoot, Jassem M. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: wound infections are associated with increased morbidity and mortality. Etiologic agents of wound infections vary with geographical locationPatients and Methods: All burn patients admitted to Specialized Burn Hospital from November 2011 to May 2012. Once fungal infection was suspected clinically, swabs were harvested for the culture of yeast. The sensitivities of the identified yeast were determined and the positive samples and cases were analyzed.Objective: This study presents Cryptococcus neoformans and their Characteristics identified from burn patients at a major Iraqi Specialized Burn Hospital.Result: The most predominant yeast isolates was Candida species which represented (56.94%), followed by Cryptococcus species (27.77%) . Twenty fungal cultures were positive for Cryptococcus species. Cryptococcus neoformanus was recorded higher percentages 8 (11.11%) follows by Cryptococcus laurentii 6 (8.33%), Cryptococcus albidus 4 (5.55%) and Cryptococcus humicola 2 ( 2.77%).Conclusion:  Cryptococcus species isolated from burn patient in a Burn Hospital in Baghdad were identified.